2018
DOI: 10.1534/genetics.118.301507
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of G1 Duration with Population Doubling Time by a Cyclin in Saccharomyces cerevisiae

Abstract: The longer cells stay in particular phases of the cell cycle, the longer it will take these cell populations to increase. However, the above qualitative description has very little predictive value, unless it can be codified mathematically. A quantitative relation that defines the population doubling time (T d) as a function of the time eukaryotic cells spend in specific cell cycle phases would be instrumental for estimating rates of cell proliferation and for evaluating introduced perturbations. Here, we show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 65 publications
2
16
1
Order By: Relevance
“…Moreover, we found a good agreement between Cln3 levels determined via the Cln3-2A-sfGFP fusion in single cells, and recently reported 27 bulk Cln3 measurements across different growth rates (Extended Data Figure 4d). Thus, Cln3-2A-sfGFP expressed from the endogenous CLN3 promoter can be used to determine Cln3 levels in single cells.…”
Section: Cln3 Concentration Increases Severalfold Around Start As a Rsupporting
confidence: 85%
See 2 more Smart Citations
“…Moreover, we found a good agreement between Cln3 levels determined via the Cln3-2A-sfGFP fusion in single cells, and recently reported 27 bulk Cln3 measurements across different growth rates (Extended Data Figure 4d). Thus, Cln3-2A-sfGFP expressed from the endogenous CLN3 promoter can be used to determine Cln3 levels in single cells.…”
Section: Cln3 Concentration Increases Severalfold Around Start As a Rsupporting
confidence: 85%
“…Comparison of single-cell Cln3 measurements with population-based Cln3 data from Blank et al 27 For Extended Data Figure 4d…”
Section: Characterization Of the Tet-on Hxt1 Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found that levels of Cln3 mRNA and protein are reduced in asynchronous cells growing under poor nutrient conditions (Gallego et al 1997;Parviz and Heideman 1998;Hall et al 1998;Blank et al 2018). However, more recent work discovered that Cln3 is also synthesized in mitosis (Landry et al 2012;Zapata et al 2014).…”
Section: Cells Growing In Poor Carbon Undergo Cell Cycle Entry At a Dmentioning
confidence: 98%
“…Distinguishing models will require a clear understanding of how changing concentrations of Cln3 and Whi5 influence cell cycle entry, and how the concentrations of Cln3 and Whi5 vary during growth and in response to changes in growth rate. However, there are conflicting reports on the behaviors of Cln3 and Whi5 during growth in G1 phase (Tyers et al 1993;Liu et al 2015;Schmoller et al 2015;Zapata et al 2014;Lucena et al 2018;Dorsey et al 2018;Blank et al 2018;Litsios et al 2019;Barber et al 2020). Most previous studies have used quantitative fluorescence microscopy to analyze protein behavior in living cells.…”
Section: Introductionmentioning
confidence: 99%